Strengthening CIS Capacity: Survey Insights to Inform the Development of AGNES Leadership and Advanced Courses - Gamoyo, Majambo Jarumani; Ahmed, Jemal Seid; Koech, Grace Jerotich; Grossi, Amanda; Ghosh, Aniruddha (Accelerating Impacts of CGIAR Climate Research for Africa, 2025)
This report summarizes the findings of a needs assessment survey conducted in April 2025 to inform the development of Climate Information Services (CIS) learning content. The survey aimed to support the design of two training initiatives: a CIS module for the 7-week online Leadership Course, and a standalone 5-week Advanced CIS Course. A total of 281 professionals from diverse sectors participated in the assessment, offering insights into their familiarity with CIS, challenges in using climate information, and preferred learning topics. Key challenges included technical complexity, limited access to data, and sectoral relevance. Participants expressed strong interest in foundational CIS concepts, interpreting climate information, service design, and policy integration. These findings directly inform the pedagogical approach and thematic content of both the leadership and advanced-level CIS offerings.